The AML1/ETO fusion protein activates transcription of BCL-2 - Klampfer, Lidija (The National Academy of Sciences of the USA, 1996)
The AML1 gene, located on chromosome 21, is involved in several distinct chromosomal translocations in human leukemia. In t(8;21) acute myelogenous leukemia (AML), the AML1 gene is juxtaposed to the ETO gene located on chromosome 8, generating an AML1/ETO fusion protein. Both AML1/ETO and the AML1 proteins recognize the same consensus DNA-binding motif (TGT/CGGT), which is found in the promoters of several genes involved in hematopoiesis. We found that two myeloid leukemia cell lines with the t(8;21) translocation, Kasumi and SKNO-1, have elevated levels of BCL-2 protein compared with other myeloid cell lines. In addition, we identified a consensus AML1 binding site in the BCL-2 promoter. Thus far, AML1/ETO has been shown to dominantly repress its target genes; however, we found that AML1/ETO activates transcription of the BCL-2 gene in U937 cells. This activation requires the presence of both the runt homology domain (rhd) and the C-terminal portion of AML1/ETO. We demonstrated sequence specific binding of both AML1A and AML1/ETO to the TGTGGT sequence in the BCL-2 promoter and showed that the AML1 binding site is required for responsiveness to AML1/ETO. Interestingly, AML1A and AML1B do not modulate the activity of the BCL-2 promoter. The elevated levels of BCL-2 in cells that express AML1/ETO may prolong their life span and contribute to the development of t(8;21) leukemia.